PERANCANGAN SISTEM INFORMASI WEBSITE PROFILE SEKOLAH SEBAGAI SARANA PROMOSI - Sari, Ani Oktarini; Kholil, Ishak (INTI Nusa Mandiri, 2025)
The development of information technology encourages educational institutions to utilize digital media in supporting promotional activities and information dissemination. This research aims to design a website-based school profile information system that functions as a promotional medium and increases the dissemination of information and expands the reach of school promotion to the community, especially prospective students and parents. This information system is designed to increase transparency, accessibility, and effectiveness in conveying school information to the public. This information system presents information about school profiles, school activities, school facilities, and school contacts in an interactive and structured manner. The Waterfall method is used in system development, which consists of the stages of requirements analysis, design, implementation, testing, and maintenance. In the needs analysis stage, the main information required is identified through interviews and surveys. Then, the interface design was made with attention to the aspects of user-friendliness and responsiveness for various devices. The implementation phase uses the codeigniter framework to build a dynamic and easy-to-manage system. Testing is carried out using the blackbox testing method to ensure that the system functionality runs according to specifications. The results of the study show that this website-based school profile information system is able to present information effectively, increase school visibility, and facilitate interaction with prospective students and parents. This system can also provide added value in building the school's image in the digital era.